Developing Role Play Learning Methods to Improve Speaking Ability in An-Nuriyah Kwanyar Bangkalan Students / Pengembangan Metode Pembelajaran Role Play untuk Meningkatkan Kemampuan Speaking pada Siswa MI An-Nuriyah Kwanyar Bangkalan - Nurul Makrifah (Al-Mudarris: Journal Of Education, 2020)
The ability to speak in English is very important for students to master the importance of English as an international language. However, the reality in Islamic Elementary School, students are not proficient in Speaking English. One of the factors is the method used does not encourage speaking skills, therefore, it is necessary to develop an English method to improve the speaking ability in Islamic Elementary  School students. This study aims to produce a role-playing method design to improve speaking skills, to describe the implementation of English methods that have been developed to improve speaking skills, to describe the effectiveness of developing English methods to improve speaking skills. This type of research is a development research with reference to the ADDIE development model which consists of five stages, including the analyze, design, develop, implement, evaluate stages. The results showed that the development design of the role play method refers to the ADDIE development model, and is based on the principles of learnin device plans development including the accuracy of coverage and accuracy of content, completeness of components, presentation of language and appropriate illustrations. The implementation of the role play method was carried out 4 times in limited trials, and 6 meetings in broad trials. The development of the role play method was declared effective by the improvement of the students' speaking skills in the psychomotor aspect with a mean pretest score of 73, and post-test 91, with an increase in N-Gain of 0.66 in the moderate category. From the cognitive aspect, the pretest results showed a mean score of 68.5, the mean post-test score was 85.75 with an increase in N-Gain 0.54 in the moderate category.